Improving the Efficacy of Liver Cancer Immunotherapy: The Power of Combined Preclinical and Clinical Studies. (8th November 2020) - Feng, Gen‐Sheng; Hanley, Kaisa L.; Liang, Yan; Lin, Xiaoxue
Abstract : Hepatocellular carcinoma (HCC) is a most deadly malignant disease worldwide, with no effective mechanism‐based therapy available. Therefore, following the "miracle" outcomes seen in a few patients at the advanced stages of melanoma or lung cancer, the immune checkpoint inhibitors (ICIs) immediately entered clinical trials for advanced HCC patients without pre‐clinical studies. Emerging data of clinical studies showed manageable toxicity and safety but limited therapeutic benefit to HCC patients, suggesting low response rate. Thus, one urgent issue is how to convert the liver tumors from cold to hot and responsive, which may rely on in‐depth mechanistic studies in animal models and large scale data analysis in human patients. One ongoing approach is to design combinatorial treatment of different ICIs with other reagents and modalities. Indeed, a phase 3 clinical trial showed that combination of atezolizumab and bevacizumab achieved better overall and progression‐free survival rates than sorafenib in unresectable HCC. This review highlights the value of animal models and the power of combining pre‐clinical and clinical studies in efforts to improve HCC immunotherapy.